The Vocabulary of Medical English a Corpus-based Study. - Panocová, Renáta (Cambridge Scholars Publishing, 2017)
The question of characterizing academic vocabulary has often been framed in a context that is purely determined by questions of language teaching. The aim in such approaches is to come up with a list of words for learners of English for Special Purposes. This book approaches this question from a more general, empirical perspective, focusing on medical vocabulary. Its main contention is that the characterization of medical vocabulary is much more complex than is suggested by a simple list. In a list, a threshold determines the borderline on a one-dimensional scale between what counts as medical.